1990
DOI: 10.1002/jhrc.1240130112
|View full text |Cite
|
Sign up to set email alerts
|

Automated on‐line HPLC‐HRGC with gradient elution and multiple GC transfer applied to the characterization of citrus essential oils

Abstract: Citrus essential oil analysis is characterized by the complexity of the separation of all the components which may belong to different classes of compounds and be present in a wide range of concentrations. Capillary GC is the best technique for characterizing the volatile fraction of citrus essential oil. In many cases, however, this technique does not achieve complete separation of all the components. A combination of LC and HRGC in off‐line methods is necessary to achieve complete resolution of the minor com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…This technique was first applied to citrus essential oil analysis by Munari et al in 1990. 53 In a later study, on-line LC-GC coupled with Fourier transform infrared spectroscopy (FTIR) was used as a sensitive approach for the determination of citropten and bergapten in a bergamot oil sample.…”
Section: Multidimensional Liquid-gas Chromatography (Lc-gc)mentioning
confidence: 99%
See 1 more Smart Citation
“…This technique was first applied to citrus essential oil analysis by Munari et al in 1990. 53 In a later study, on-line LC-GC coupled with Fourier transform infrared spectroscopy (FTIR) was used as a sensitive approach for the determination of citropten and bergapten in a bergamot oil sample.…”
Section: Multidimensional Liquid-gas Chromatography (Lc-gc)mentioning
confidence: 99%
“…53 In a later study, on-line LC-GC coupled with Fourier transform infrared spectroscopy (FTIR) was used as a sensitive approach for the determination of citropten and bergapten in a bergamot oil sample. 54 Figure 9 illustrates (a) the HPLC separation of the bergamot oil, (b) the GC separation of the target analytes employing FID, and (c) FTIR detection.…”
Section: Multidimensional Liquid-gas Chromatography (Lc-gc)mentioning
confidence: 99%
“…have been outlined in many publications [ 12, and, in comparison with off-line methods, it offers a number of advantages: the amount of sample required is much lower; no sample work-up, evaporation, or dilution is needed when liquid samples are analyzed; and very complex sample pre-treatment is possible in a fully automated way. The analysis of essential oils presupposes transfer via a retention gap [22-251 because such samples contain volatile components requiring analysis temperatures starting at 45°C.…”
Section: Introductionmentioning
confidence: 99%
“…The simple mixtures thus obtained are easier to resolve without problems of peak overlap. It has been shown that the use of grade I1 activity neutral alumina as adsorbent, and light petroleum, light petroleum/diethyl ether, and diethyl ether as eluents [12] permits better fractionation of the essential oils into compound classes (hydrocarbons, esters, carbonyl compounds, and alcohols) than other systems such as distillation or preparative gas chromatography [ Figure 1. Schematic of the LC-Gc-MS inte@ace.…”
Section: Introductionmentioning
confidence: 99%
“…The determination of carbonyl compounds in analytical chemistry is becoming always more important for the monitoring of formation reactions or the transformation of aldehydes [ l ] and for the study of the fractions of the volatile compounds responsible for the organolectic characteristics of natural aromas and flavoring agents [2,3].…”
Section: Introductionmentioning
confidence: 99%